Reflexionsseismiska mätningar över Burträsk-förkastningen: Original stack - Juhlin, Christopher; Lund, Björn (Swedish National Data Service, 2019)
In 2008, a 22 km long high resolution reflection seismic profile was acquired over the Burträsk fault in Northern Sweden. The Burträsk fault formed at the end of the last glacial, triggered by the rapid melting of the Scandinavian ice sheet and the following crustal rebound. The aim of the survey was to image the structure of the fault with depth. The profile followed existing roads resulting in a very crooked acquisition geometry. A list of the key acquisition parameters is given below. The dataset was first processed and published in 2011. In 2018, the dataset was reprocessed using an additional cross-dip correction step to improve the imaging of reflection with a dip component in the cross-profile direction. The following data files are available for downloading: 1) raw shot gathers (decoded and quality controlled, with geometry information in the headers) 2) original stacked section from Juhlin and Lund (2011) 3) cross-dip corrected stacked section from Beckel and Juhlin (2019) 4) cross-dip corrected migrated section from Beckel and Juhlin (2019) A short summary of the main processing steps for each dataset is given below. For a complete description, please refer to the above mentioned publications. Key acquisition parameters: Number of channels: 280 Near offset: 0 m Geophone spacing: 20 m Geophone type : 28 Hz single Nominal source spacing : 20 m Source type : VIBSIST Hit interval between hammer blows : 100-200 ms Sweeps per source point :3-4 Nominal fold : 140 Recording instrument : SERCEL 408L Sample rate : 1ms Field low cut : Out Field high cut : 400 Hz Record length : 23 s Profile length : 22 km Source points : 799 Dates acquired: 2008/08/05-2008/08/16 Short summary of the main processing steps: 1) BUR_shots_geom.sgy The raw shot records are pre-processed with VIBSIST decoding, quality control. Information about the shot and receiver geometry has been added to the trace headers. 2) BUR_original_stack.sgy The processing flow of the original data stack includes trace editing and balancing, spectral ...